2022
DOI: 10.3390/cancers14153700
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Localization in Human Large Extracellular Vesicles for the EGF-CFC Founder Member CRIPTO and Its Biological and Therapeutic Implications

Abstract: Tumor growth and metastasis strongly rely on cell–cell communication. One of the mechanisms by which tumor cells communicate involves the release and uptake of lipid membrane encapsulated particles full of bioactive molecules, called extracellular vesicles (EVs). EV exchange between cancer cells may induce phenotype changes in the recipient cells. Our work investigated the effect of EVs released by teratocarcinoma cells on glioblastoma (GBM) cells. EVs were isolated by differential centrifugation and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…Recent studies have identified CRIPTO in tumor-derived EVs (TEVs) in several cancer types 20, 24 . To determine whether CRIPTO was likely to be present in EVs within the TME of breast cancers in our system, we reanalyzed MDA-MB-468 xenograft tumors for expression and localization of CRIPTO and the canonical EV marker CD81 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified CRIPTO in tumor-derived EVs (TEVs) in several cancer types 20, 24 . To determine whether CRIPTO was likely to be present in EVs within the TME of breast cancers in our system, we reanalyzed MDA-MB-468 xenograft tumors for expression and localization of CRIPTO and the canonical EV marker CD81 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified CRIPTO in TEVs in several cancer types 18,22 . To determine whether CRIPTO was likely to be present in EVs within the TME of breast cancers in our system, we reanalyzed MDA-MB-468 xenograft tumors for expression and localization of CRIPTO and the canonical EV marker CD81 23 Next we asked whether CRIPTO overexpression could be leveraged to promote delivery of selected payloads to recipient cells.…”
Section: Cripto Drives Ev Uptake By Recipient Fibroblastsmentioning
confidence: 99%
“…We have performed the isolation of SCPs from the media in which the cells had grown by differential ultracentrifugation. We have used a protocol that is common for harvesting small extracellular vesicles [58]. We have assessed samples by interference light microscopy and visualized them by cryogenic electron microscopy [59].…”
Section: Discussionmentioning
confidence: 99%
“…SCPs were isolated by differential centrifugation, using a protocol widely used for the isolation of small extracellular vesicles [ 63 ]. Briefly, the cells were removed by low-speed centrifugation (300× g , 10 min, 4 °C, centrifuge Centric 260R with rotor RA 6/50 (Domel, Železniki, Slovenia)), using 50 mL conical centrifuge tubes (ref.…”
Section: Methodsmentioning
confidence: 99%